If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 5x = -1 Solving 9 + 5x = -1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 5x = -1 + -9 Combine like terms: 9 + -9 = 0 0 + 5x = -1 + -9 5x = -1 + -9 Combine like terms: -1 + -9 = -10 5x = -10 Divide each side by '5'. x = -2 Simplifying x = -2
| 3/4x-5=7/12 | | 9x-22=23 | | x^2+36=x^2-74 | | -186+10x=-4x+80 | | X^3-6x^2-7x+42=0 | | 3x-8=x+25 | | 9-2(x)=35 | | 11+17x=29+14x | | 5=4m+14b | | 4.25/x=0.4545454545 | | 11p=2 | | 4/7(48046)-272 | | 200+15x=77 | | x+3=7x+51 | | (x-(5/6))^2 | | 12=4(d-2) | | 100=80(1+1.5n) | | 10x-2x=30-3x | | 4x-2(x-4)=-3+4x+1 | | c=4/7(48046)-272 | | (2x)2-x-1=0 | | 3x-17=-50 | | y=-3cosx+2sinx | | 6x-6+4x=3 | | 2x-x+5(x+4x)-8-9=20 | | 2x-5x+5(x+4x)-8-9=20 | | 4x*5x=270 | | 17-9+4+6x=19 | | 4x-5(2x+5)=4(x+3) | | 4/3•64 | | 5x-4+-2x+3=-7+-3x+5+2x | | 8x+2x+30=180 |